ANALISIS STRUKTUR, PERILAKU DAN KINERJA PASAR (Structure, Conduct and Market Performance) KOMODITI PADI DI DESA BUNGA RAYA DAN DESA KEMUNING MUDA KECAMATAN BUNGA RAYA KABUPATEN SIAK - Ari Jolanda Saputra; Jum'atri Yusri; Novia Dewi (Fakultas Pertanian, Universitas Riau, 2017)
This study aimed to analyze the marketing of rice in Bunga Raya Village and Kemuning Muda Village in Bunga Raya District using a structural, behavioral and market performance approach. The research location was determined by purposive sampling, namely two villages which were the centers of rice production. Respondents from this study were rice farmers and all marketing institutions involved in marketing rice from farmers as producers to wholesalers as consumers. The results show that there are three channels of rice marketing, namely marketing channels I, farmers sell to collectors, then collectors sell to wholesalers, marketing channels II, farmers sell to collectors who have mobile rice milling and marketing channels III, farmers sell to wholesalers. The market structure of rice that occurs is the oligopsonic market, judging by the relatively small number of buyers, then viewed from the market share value, concentration ratio and the Herfindhal Index of each trader shows a value that is not too different. Farmers as producers are price takers which results in the rate of price changes at farmers as producers are smaller than the rate of price changes at the level of wholesalers as consumers. The marketing margin seen from each marketing channel that occurs shows that the largest margin and profit are obtained by traders who perform more marketing functions.